P008 Fibrostricturing Crohn's disease is characterised by an imbalance in active eosinophils, Th1, Th2 and regulatory T cells. (30th January 2023) - Jacobs, I; Ke, B J; Cremer, J; D'Hoore, A; Bislenghi, G; Matteoli, G; De Hertogh, G; Sabino, J; Ferrante, M; Vermeire, S; Breynaert, C; Vanuytsel, T; et al.
Abstract: Background: About one third of patients with Crohn's disease (CD) develop strictures during their disease course requiring surgical resection. The immune landscape involved in this process is poorly understood. Therefore, we aimed to characterise the fibroblast phenotype, immune cells and their mediators involved in intestinal strictures. Methods: We included 25 CD patients with stricturing disease in the terminal ileum (TI) and 10 controls with colorectal cancer (CRC), all undergoing an ileocolonic resection. Transmural samples from the resection specimen of the TI were obtained. Macroscopically, CD tissue was divided into unaffected, fibrostenotic and inflamed regions by an experienced histopathologist. Next, mucosa was separated from deeper layers, after which single cells were isolated and fluorescently stained for flow cytometry. Protein levels were determined via the MesoScale Discovery (MSD) platform in the corresponding samples. Comparisons between CRC controls and CD patients were performed via an unpaired t-test or Mann-Whitney analysis and corrected for multiple testing. Results: An increase in active fibroblasts and decrease in inactive fibroblasts in the fibrotic and inflamed mucosa (p=0.0002 and p<0.0001) and deeper layers (p=0.003 and p=0.02) when compared to the CRC controls was observed, confirming ongoing tissue remodelling. An enrichment of active eosinophils was only seen in the fibrotic deeper layers (p=0.02), although an increase in T helper 2 (Th2) cells was observed in both the fibrotic and inflamed deeper layers (p=0.02 and p=0.04). In contrast, T helper 1 (Th1) cells were decreased in both fibrotic and inflamed mucosa (p=0.03 and p=0.02) and deeper layers (p=0.01 for both). Regulatory T cells were significantly enriched in both fibrotic and inflamed mucosa (p<0.0001 and p=0.0005) and deeper layers (p=0.01 and p=0.006) (figure 1). Protein quantification confirmed a significant increase in transforming growth factor-β3 (TGF-β3) in the fibrotic (p=0.007) and inflamed (p=0.0002) layers, but not in the more superficial mucosa. Comparably, IL-1β was increased in the fibrotic (p=0.05) and inflamed (p=0.05) deeper layers. A similar observation was made for basic fibroblast growth factor (bFGF) (p=0.004), although only a trend could be seen in the fibrotic deeper layers (p=0.08) (figure 2). Conclusion: The fibrotic and inflamed tissue of CD patients is characterized by increased activated eosinophils, Th2 and regulatory T cells and decreased Th1 cells, as well as many of their mediator cytokines. The current immunological characterisation can help to prioritise potential anti-fibrotic targets for stricturing CD.